A Different Living Circumstances of Longmen School in the Early Qing Dynasty——An Analysis of Pan Jingguan and His Work DaoDeJingMiaoMenYue / : Liu Gusheng, Wang Chuang - Liu, Gusheng.
Zhu Yuanyu, who is a taoist priest of Longmen shcool, has been in Changzhou for a long time before Wang Changyue came to Jiangnan. One of Zhu Yuanyu’s apprentice named Pan Jingguan with his life shows us a different living circumstances of Longmen school in the early Qing Dynasty. Pan is the fifth generation successor of Longmen school without doubt, his work DaoDeJ ingMiaoMenYue revealing the features of Quanzhen school, but he also considers himself to be a heirs of Jingming shcool and Taiyi school. As a member of Longmen school, Pan Jingguan does not try to develop Longmen school, instead, he interacts with the other schools of Taoism and folk beliefs which makes his identity complicated. The observation of Pan could bring us a new understanding about the Longmen school in the early Qing Dynasty